2007
DOI: 10.1007/s11064-007-9303-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phenylalanine and its Metabolites on Cytoplasmic Free Calcium in Cortical Neurons

Abstract: Classic phenylketonuria (PKU) is characterized by brain lesions. However, its underlying neurotoxic mechanisms remain unknown. Based on our previous studies, we hypothesized that calcium might participate in PKU-associated neuropathy. In cultured cortical neurons, cytoplasmic free calcium concentration ([Ca(2+)](i)) decreased dramatically when treatment with phenylalanine (Phe) and phenyllactic acid, while phenylacetic acid treatment immediately increased [Ca(2+)](i), which began to decrease after 3 min. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Moreover, Phe treatment can decrease free Ca 2+ (Yu et al . ). This situation was different in the peach plants used for PPV assays.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Phe treatment can decrease free Ca 2+ (Yu et al . ). This situation was different in the peach plants used for PPV assays.…”
Section: Discussionmentioning
confidence: 97%
“…Rat models of hyperphenylalaninemia have demonstrated that Phe can directly inhibit enzyme activity within all energetic pathways in the brain, including glycolysis, tricarboxylic acid cycle, respiratory transport chain, phosphocreatine-creatine metabolism, and ketone body synthesis and utilization. Alternately, sustained elevations of blood Phe could indirectly trigger the aforementioned bioenergetic changes by enhancing the production of reactive oxygen species ( 26 ) and modulating the activity of the plasma membrane Ca 2+ -ATPase ( 27 ). The resulting accumulation of reactive oxygen species and calcium not only enhances cellular vulnerability to oxidative damage ( 28 ), but can also change the activity of key enzymes involved in energy metabolism ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, sustained elevations of blood Phe could indirectly trigger the aforementioned bioenergetic changes by enhancing the production of reactive oxygen species ( 26 ) and modulating the activity of the plasma membrane Ca 2+ -ATPase ( 27 ). The resulting accumulation of reactive oxygen species and calcium not only enhances cellular vulnerability to oxidative damage ( 28 ), but can also change the activity of key enzymes involved in energy metabolism ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…These alterations were not reverted by Phe-restricted diet [99]. In another study, Yu and colleagues [100] demonstrated that Phe alters intracellular free calcium concentrations by modulating plasma membrane Ca 2+ -ATPase in cortical neurons.…”
Section: Calcium Homeostasismentioning
confidence: 99%